Effect of phosphorus on root growth, root to shoot ratio, phosphorus uptake and use efficiency in some barley genotypes as influenced by phosphorus fertilization - Abdalgader, Kamal. A. Abdalgader; Amgada, Suad. A.; Amgada, Eman. A. (Journal of Pure & Applied Sciences, 2022)
Root are important organs that supply phosphorus to growing plants. Data related to root growth and P- uptake by some barley genotypes are limited. A pot experiment was conducted in Faculty of Agriculture Omar –AL-Mukhtar University to evaluate the Effected phosphorus on root growth of different barley varieties during the growing season (2021). The objective of this study was to evaluate root growth of some barley genotypes and P-uptake and use efficiency under phosphorus (P) levels. A randomized complete block design was used in a factorial arrangement and the treatments were replicated three times. The P levels used were 0(low), 50 (medium) and 100 (high) mg kg-1 of soil, and four barley genotypes were evaluated. Root dry weight g plant-1, contribution of root in the total plant weight (%), root/ shoot ratio and P- uptake and use efficiency were significantly influenced by P and barley treatments. Maximum values of these root growth parameters were achieved with the addition of 50 mg P kg -1 soil. The P × barley genotypes interactions for P-uptake and use efficiency were significant, indicating variation in uptake pattern of P by barley genotypes with the variation in P rates. Increase in root growth with the addition of P can improve P uptake from the soil and lessen loss of nutrient from the soil and plants systems.